Papa's baby : paternity and artificial insemination - Lewis, Browne (New York : New York University Press, 2016)
In 'Papa's Baby', Lewis argues that the courts should take steps to insure that all children have at least two legal parents. Additionally, state legislatures should recognize that more than one class of fathers may exist and allocate paternal responsibility based, again, upon the best interest of the child.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Paternity -- United States; Artificial insemination, Human -- Law and legislation -- United States; Children -- Legal status, laws, etc. -- United States; Law; United States of America, USA; Sociology: family & relationships; Laws of specific jurisdictions & specific areas of law; Family law: children